Insider Trading Case Settlement: Studies in Indonesia and The United States - Gea, Mansix Agusmanto; Hutajulu, Marihot Janpieter (Wacana Hukum, 2022)
Insider trading is a term that refers to the practice in which corporate insiders conduct securities transactions (trading) using their exclusive information that is not yet available to the public or investors. Indonesia and the United States are 2 (two) countries that prohibit insider trading in the capital market. Through this article, the author wants to analyze the similarities and differences the regulation of insider trading in Indonesia and the United States, and explain the legal process for the settlement of Insider Trading cases in Indonesia and the United States. This research is a normative research, using the laws and regulations on the capital market originating from 2 (two) countries, there are the laws and regulations on the capital market of Indonesia and the United States. The analysis of this paper concludes that Indonesia and the United States prohibit the practice of insider trading in the capital market.